The Cambridge companion to Gadamer - Dostal, Robert J. (Cambridge University Press, 2002)
Hans-Georg Gadamer (b. 1900) is widely recognized as the leading exponent of philosophical hermeneutics. The essays in this collection examine Gadamer's biography, the core of hermeneutical theory, and the significance of his work for ethics, aesthetics, the social sciences, and theology. There is full consideration of Gadamer's appropriation of Hegel, Heidegger and the Greeks, as well as his relation to modernity, critical theory and poststructuralism.